Photography Technique in Gawai Nyobeng Ritual - Teddy Albert, Javeril (2019)
This basic research is intended to expand knowledge and increase the understanding of fundamental principles. The aim of this research is to explore the possibilities in conducting ethnography based on visual art and compositional interpretation points of view. The outcome of the visual data collected in ethnography research will be discuss. The researcher suggest, by implementing the concepts and theory of visual arts and compositional interpretation into the process of the collection of visual data in ethnography research will improve the findings of the research especially on the visual data collection. The discussion was established on the culture of the ethnic of Bidayuh from Bau, Sarawak, Malaysia, that still practice the ancient belief of their ancestors. To be exact, Gawai Nyobeng of the Bidayuh are the subject of study. The relationship between visual arts, compositional interpretation are discuss to get in-depth understanding about how their methods can be used in ethnography research. All involving topics about ethnography, visual arts, and compositional interpretation is being discussed in order to give the general description about their current situations in the academic world.